HUBUNGAN PARITAS DENGAN JENIS HISTOPATOLOGI KARSINOMA SERVIKS UTERI DI RSUP Dr. SARDJITO YOGYAKARTA - , Anyta Rahmawati ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Eighty-five percents of the incidence of cervical cancer occur in developing countries. The number of patients with cervical cancer in Dr. Sardjito General Hospital has increased every year. Histopathological types are considered as one of the prognostic factors of cervical cancer. The prognosis of cervical adenocarcinoma is worse than squamous cell carcinoma. Cervical adenocarcinoma is found to be less than the squamous cell carcinoma, but the incidence tends to increase. Risk factors that could potentially increase the prevalence of cervical adenocarcinoma are nuliparity and obesity. Objective: To obtain evidence of a relationship between parity and histopathological types of cervical carcinoma. Methods: The study design used case-control study of quantitative approach. The subjects were cervical carcinoma patients at Dr. Sardjito General Hospital, registered from 1 January 2006 to 31 December 2007. The sampling technique was done by non probability sampling with a type of purposive sampling. The data used secondary data of the medical records of patients with cervical cancer. The data collection used checklists. The analysis of data was through three stages, namely univariable analysis, bivariable analysis using chi-square and multivariable analysis using logistic regression. Results: The analysis showed a significant relationship between parity and histopathological types of cervical carcinoma (OR: 2.48, 95% CI: 1.06 to 6.07). Parity of 0-4 was at higher risk of cervical adenocarcinoma, while the parity of more than four was at risk of squamous cell carcinoma. Age, education level, age at first marriage and Body Mass Index were not related to the types of cervical carcinoma. Conclusions: Parity with the cutoff point of four was associated with histopathological types of cervical carcinoma.